Consonant Deletion in the Speech of English-Platoid Bilinguals - ., Unubi; Abraham, Sunday (European Journal of Applied Sciences, 2019)
This paper, which examines consonant deletion in the speech of English-Platoid bilinguals, is in the domain of articulatory phonetics. When English words end in two or three consonants, speakers of English who are native speakers of Platoid languages usually delete consonants word finally during articulation. This has been of deep interest to the researcher, and therefore decides to investigate the phenomenon that leads to this incidence as a way of proffering a linguistic explanation to it. To do this, a total of twenty-two sentences containing words that end in two or three consonants were used as data elicitation technique from some English-Platoid bilinguals. These words were noted by the researcher during informal daily conversations at different occasions. The words whose consonants got deleted at the word final position were transcribed phonetically for purposes of clarity. The second part of the data constitutes the elicitation of six words of common nouns each from ten indigenous Platoid languages. Since the focus is on consonant deletion, few consonant systems of these languages were also presented. This is so done with a view to discovering whether there is evidence of consonant cluster in those languages or not, especially at word final position in order for the researcher to pin down the factor responsible for the deletion. From there, the study concludes that there is no evidence of consonant cluster at word-final positions in Platoid languages, and where it does, it only exists as digraph orthographically, as in: shīk-bīsh ‘sin’, kàt-ɗang ‘if’ (Mwaghavul); kámbo̟ng ‘cocoyam’ (Ron); ìsho̟sh ‘honey bee’, nànámàng ‘girls’ (Afizere); ìkpáng ‘plate’, ǹding ‘water’ (Tarok), etc.